Pemetaan Potensi Desa untuk Penyusunan Masterplan Desa berbasis Desa Mandiri Budaya di Kalurahan Bangunharjo - Pabulo, Azfa Mutiara Ahmad; Astuti, Tutut Dewi; Setyaningsih, Putry Wahyu (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
Bangunharjo Village is an agricultural village, and 50% of its population works as farmers. Because it is difficult to maximize the potential of tourism, culture, and MSMEs to achieve the status of an Independent Cultural Village. The purpose of this community service project is to compile a list of resources owned by rural villages, such as agricultural land and infrastructure (physical assets) as well as local knowledge and institutions (non-physical assets). This list will be used to compile an integrated village master plan. The participatory methods used involve BUMKal, training for survey officers, data collection based on zoning, and the use of technology. The total area of rice fields found is one hectare, with the potential of the Code River and 17 small and medium enterprises (SMEs) that have not been utilized. The community master plan will include four main sections: Cultural Community, Tourism Village, Entrepreneurial Village, and Main Village. Digital training for BUMKal, e-commerce growth, and collaboration with local governments are ideas to make things more sustainable. This project demonstrates that asset-based and participatory strategies can help villages develop inclusively and sustainably. The final outcome of this activity is the development of a village master plan as a guideline for the development of Bangunharjo Village toward a Culturally Independent Village.